Electrochemical synthesis of dipyrazolo/dipyrimidine-fused pyridines via oxidative domino cyclization of C(sp3)–H bonds. Issue 6 (11th February 2022) - Qian, Peng; Xu, Linna; Wang, Wenyan; Zhang, Lin; Tang, Liang; Liu, Jiaojiao; Sheng, Liangquan
Abstract : An electrochemically oxidative domino cyclization reaction of methyl azaarenes/ketones with pyrazol-5-amines and 6-amino-pyrimidine-2, 4-diones was developed, providing a variety of dipyrazolo/dipyrimidine-fused pyridines with moderate to good yields. Abstract : An electrochemically oxidative domino cyclization reaction of methyl azaarenes/ketones with pyrazol-5-amines and 6-amino-pyrimidine-2, 4-diones was developed, providing a variety of dipyrazolo[3, 4- b :4′, 3′- e ]pyridines and dipyrimidine-fused pyridines with moderate to good yields. The reaction involved two C–C bond formations and one C–N bond formation in one pot. Moreover, the photoluminescence properties of the representative dipyrazolo[3, 4- b :4′, 3′- e ]pyridines were investigated.